Luxation injuries in immature permanent teeth - epidemiologic study - Ioana-Andreea Stanciu; Mihaela Tănase; Rodica Luca; Daciana-; Ruxandra Lipan; Aneta Munteanu (Amaltea Medical Publishing House, 2020)
Objectives. To assess distribution and complications of luxation injuries (LI) of immature permanent teeth (IPT) in a sample of children from a universitary dental clinic. Material and method. Retrospective descriptive observational study using the files of 68 children (37 boys) aged 6-12 years (mean age = 8.62±1.75 years) diagnosed with LI of IPT in the Pedodontics Department, Bucharest between 2010 and 2019. The patients' distribution according to age, gender, etiological factor and the number of affected teeth was evaluated. The distribution of traumatized teeth was assessed according to the type of injured teeth, the type of LI, the treatment performed and the complications over time. Data were statistically analyzed with SPSS 18.0, with ANOVA and t-test (p < 0.05). Results. Children aged 7-8 years were most affected (54.40%). Boys were more affected than girls (54.41% versus 45.59%) (boys:girls = 1.19:1) (NS, p > 0.05). Most frequent causes of injuries were falls (51.47%). 48.52% of children had 1 injured tooth, 35.29% - 2 teeth, 16.17% - 3-5 teeth, upper central incisors being the most commonly involved (73.17%). Type of trauma: subluxation - 39.02%, lateral luxation - 20.32%, intrusion - 13.82%, extrusion- 9.75%, avulsion - 8.95%, concussion - 8.14%. Treatment: monitor only - 59.34%, repositioning/replantation and splinting - 40.66%. Post-traumatic complications: in 23.14% of re-evaluated teeth - pulpal involvement, 20.36% root resorption. Discussions. From the analysis of the results, it was observed that in the studied group the age at which the most traumas occurred was 7-8 years. As a rule, it was found that injuries are more common at the age of 7-9 years, when children begin to practice many sports, and 10-12 years, respectively, when they gain a great confidence in their own abilities and take great risks on their own. Regarding the etiology of periodontal trauma, the research showed that, for more than half of the patients, the etiological factor was the accidental fall from walking/running, followed by accidents at the playground and accidents with bicycles or rollers. Conclusions. It is necessary to inform parents, teachers and coaches regarding the importance of early attending a specialized dental care office for patients with luxation injuries, as well as on the regular check-ups for early detection and treatment in case of complications.